Bouncing Spallation Bombs During the 2021 La Palma Eruption, Canary Islands, Spain - James M. D. Day; Harri Geiger; Valentin R. Troll; Francisco J. Perez-Torrado; Meritxell Aulinas; Guillem Gisbert; Juan Carlos Carracedo (Earth Science, Systems and Society)
Incandescent pyroclasts of more than 64 mm in diameter erupted from active volcanoes are known as bombs and pose a significant hazard to life and infrastructure. Volcanic ballistic projectile hazard assessment normally considers fall as the main transport process, estimating its intensity from bomb location and impact cratering. We describe ballistically ejected bombs observed during the late October 2021 episode of eruption at La Palma (Canary Islands) that additionally travelled downhill by rolling and bouncing on the steep tephra-dominated cone. These bouncing bombs travelled for distances >1 km beyond their initial impact sites, increasing total travel distance by as much as 100%. They left multiple impact craters on their travel path and frequently spalled incandescent fragments on impact with substrate, leading to significant fire hazard for partially buried trees and structures far beyond the range of ballistic transport. We term these phenomena as bouncing spallation bombs. The official exclusion zone encompassed this hazard at La Palma, but elsewhere bouncing spallation bombs ought to be accounted for in risk assessment, necessitating awareness of an increased hazard footprint on steep-sided volcanoes with ballistic activity.